Pengaruh Model Talking Stick Terhadap Hasil Belajar pada Mata Pelajaran Matematika di Kelas IV SD - Fernanda, Aldi Rizky; Tanzimah, Tanzimah; Akhbar, M.Taheri (Indonesian Research Journal on Education, 2023)
The learning model is one of the learning components that becomes a guide in carrying out the activity steps. In applying the steps of the learning model there are approaches, strategies, methods, techniques, and tactics used by teachers to support learning. One of the learning models that can be used is the talking stick model. The talking stick model is a learning model that can encourage students to dare to express their opinions. This learning model uses the help of a tool in the form of a stick, where students who receive sticks must dare to answer questions from the teacher and express their opinions. elementary school. The research method used in this research is quantitative with experimental methods. Data collection techniques used by researchers in this study were tests and documentation. The data obtained were then calculated using the SPSS application. 25. Thecriteria for testing this research hypothesizes that Ha is accepted if account> t table. an account is5.026 and t-table is 2.002 then Ha is accepted. The results of this study indicate that there is asignificant effect of the talking stick learning model on learning outcomes in mathematics in the fourth grade of elementary school.